Urban Development Boundary Setting Versus Ecological Security and Internal Urban Demand: Evidence from Haikou, China - Luoman Pu; Qi Xia (Land, 2023)
Amidst rapid urbanization, the conflict between urban population and land is intensifying due to ecological degradation and imbalanced supply and demand of land resources in and around cities. Demarcating the urban development boundary is a specific measure to regulate the scale and form of urban expansion while considering internal urban demand as well as ecological security. This study took Haikou City, China, as the study area, exploring a new way to take into account the external constraints and endogenous mechanisms of urban expansion, constructing a comprehensive ecological security pattern (ESP) using the MCR model, demarcating recent rigid development boundaries, and demarcating future elastic development boundaries using the CA–Markov model. The results were the following: (1) By identifying the current urban boundary in 2020, the urban land area of Haikou City was found to be 261.64 km2. (2) Using the MCR model to construct comprehensive ESP and demarcate a rigid development boundary revealed that the total area within the boundary was 398.37 km2, with an additional growth potential of up to 136.73 km2. (3) Demarcating elastic boundaries for Haikou City in 2030, 2040 and 2050 using the CA–Markov model while considering natural and socio-economic driving factors and constraints showed the internal areas within these boundaries to be calculated at 451.80, 489.46 and 523.37 km2, respectively, which were higher than that in 2020 by 190.16, 227.82 and 261.73 km2. (4) Some suggestions, such as establishing a comprehensive technical system, ensuring robust policy support and legal protection, and improving the responsibility management system, were proposed in the implementation of urban development boundaries. Scientifically and reasonably demarcating the recent rigid urban development boundary and future elastic urban development boundaries can ensure sustainable urban development while preserving the ecological environment and satisfying urban development demand.